The development and evaluation of a homemade laparoscopic endotrainer using the IDEAL framework and MISTELS scoring system: a pilot study - Malik, Muhammad Usman; Connelly, Tara M.; Awan, Naila Akhtar; Bhatti, Fatima Rizwan; Hayat, Rana Saddaqat; Awan, Hafiz Riaz Hussain (ANZ journal of surgery, 2024)
Background A prospective IDEAL stage 2a pilot study was carried out at a tertiary care center to evaluate the reliability of a homemade laparoscopic endotrainer, following the MISTEL and IDEAL framework guidelines. Methods The validated modified (MISTELS) score was used to test the reliability of a low‐cost laparoscopic trainer with commonly found components built by surgeons. Basic household materials including a cellular phone (camera source), wifi (linking source) and freely available webcam apps were used for construction. Five basic laparoscopic skills were performed by general surgery resident volunteers with minimal (1–6 months') laparoscopic surgery experience and tested and retested based on efficiency and precision. To determine interrater reliability, two trained observers scored all subjects. The Cronbach alpha test was used to test for internal consistency between tasks. The Interclass correlation coefficient is used for test and retest reliability. Results 15 (80% male, mean age 28 ± 5 years) residents were included. The interrater and test–retest reliabilities for the total scores of the basic laparoscopic skills tests were 0.952 (95% CI, 0.895–0.981) and 0.64 (95% CI, 0.35–0.77), respectively. The Cronbach Alpha for the first assessment test and retest was 0.83. The MISTELS metrics had excellent reliability, exceeding the threshold level of 0.8. Conclusion It is possible to assemble a low‐cost, reliable trainer at home to enhance laparoscopic skills during residency. The development and evaluation of a homemade laparoscopic endotrainer using the IDEAL framework and MISTEL scoring system: a pilot study